1990
DOI: 10.1183/09031936.93.03010055
|View full text |Cite
|
Sign up to set email alerts
|

The action of platelet activating factor and its antagonism by WEB 2086 on human isolated airways

Abstract: This study investigated the direct and indirect effects of platelet activating factor (PAF, PAF-acether) on human isolated airways. PAF caused a single non-repeatable contraction which was found to be variable both between lung samples and within tissues from the same lung. The range of contractions induced by PAF, 7 X 10(-8), M and 7 X 10(-7) M was 2-55% and 3-72% of the maximal response to carbachol, respectively. The PAF antagonist WEB 2086, 10(-6) M, inhibited the contraction induced by PAF, 7 X 10(-7) M, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
2
8
1
Order By: Relevance
“…that contraction of human isolated bronchus induced by PAF is not related to the release of mediators [Tom secondary cells. Hence, the variability of the responses to PAP, observed in this study and previous studies [25,30] may not be due to bronchial tissue dwelling cells but rather to a direct effect of the mediator.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…that contraction of human isolated bronchus induced by PAF is not related to the release of mediators [Tom secondary cells. Hence, the variability of the responses to PAP, observed in this study and previous studies [25,30] may not be due to bronchial tissue dwelling cells but rather to a direct effect of the mediator.…”
supporting
confidence: 55%
“…Clearly, more studies are needed before the conclusions drawn by JoHNSON et al [29,30] can be fully accepted. Whether or not airway smooth muscle is affected by PAF directly, the potential s ignificance of PAF remains.…”
mentioning
confidence: 98%
“…The variability in the PAP responses observed in vivo [7,18] and in vitro [4] suggests that PAF may be having an indirect mode of action. SMITH et al [7) observed intersubject variability in the PAF response in vivo, which they suggested was due to an indirect mechanism of action of PAF.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that PAF causes a variable contraction of human isolated airways [4] . Because of the variable nature of this response, we propose that the in vitro PAP-induced effects are secondary to the release of mediators from inflammatory or epithelial cells .…”
mentioning
confidence: 97%
See 1 more Smart Citation